Malignant Melanoma of Foot with Brain Metastasis – Case report - Thapa, Dinesh Kumar; Singh, Sunil; Tamrakar Karki, Karuna; Rai, Ujwal; Shrestha, Manmohan (Eastern Green Neurosurgery, 2024)
Melanoma is a rare type of skin cancer which has a strong correlation between occurrence and exposure to sun ultraviolet radiation. Though being uncommon, it has the highest mortality rate of all skin cancers. The patients with advanced disease may have higher mortality rates. The formation and development of melanoma metastases to brain are not fully understood. The most accepted way is the presence of oncogenic BRAF mutation, which occurs in up to 50% of metastatic melanoma patients. There was a lower survival rate in metastatic melanoma before detailed pathophysiology was understood. There are new research going on immunotherapy and targeted therapy to improve the prognosis of melanoma patients. Hereby, we would like to present a case of melanoma of foot with distant metastasis to brain.